Agri-Farm Tourism in Region IV-A: Basis for a Proposed Development Plan - Salarda, Lady Michelle dP. (Future Science / FSH-PH Publications, 2021)
Agri-Farm tourism in Region IV-A is very evident because of its rich farm lands. It is an indication that it gets to produce jobs and income to its people and the community at large. In order to develop sustainable Agri-farm tourism in Region IV-A, the study suggested variety of projects, strategies and activities to be implemented contributing to the environmental, cultural, social and economic growth of the area that is reflected through a development plan. The study was conducted to determine what are the products, services, marketing activities and linkages in Agri-farm tourism in Region IV-A, and assess its economic contributions to the region, as well as its capability to be sustainable. Likewise, the researcher come up with any recommendations that will improve the products, services, marketing activities and linkages of Agri-farm tourism in the region and will contribute to its possible sustainability based or anchored purely from the results of the study. The descriptive method of research was employed in this study. The respondents such as farm owners, Local Government Unit employees and visitors were randomly chosen and asked to answer the survey questionnaire about their perceptions on the products, services, marketing activities, linkages and the problems encountered in the selected Agri-Farm Tourism sites located in Region IV-A. Responses were analyzed using percentage, weighted mean, Analysis of Variance, Ranking, and to assess whether there is a significant difference in the responses of the three groups of respondents, use the t-test (Grouped Data).The results showed that the respondents looked for a more sustainable products, services, marketing activities and linkages. In the acceptability of the Development Plan, it was found to be highly acceptable by the respondents and can be implemented by the Agri-farm tourism owners for sustainable development. These results suggest that owners and the management should consider improving the Agri-farm tourism business with strong emphasis on the products, services, marketing activities and linkages to attain higher assessment rating from Very Good to Excellent. The Proposed Development Plan may be adopted by the Agri-Farm Tourism planners, farm owners and Local Government Unit employees should give emphasis on Agri-farm Tourism offer as to products and services, extent of marketing and linkages, and its sustainability to keep the Agri-farm tourism business.